THE THE SYMBOLIC MEANING OF WEDANG UBLEK TRADITION IN THE HAUL OF MBAH ABDUSSHOMAD JOMBOR IN CIPETE VILLAGE, CILONGOK DISTRICT, BANYUMAS REGENCY: A PAUL RICOEUR'S HERMENEUTIC PERSPECTIVE - Ida Novianti; Farah Syiva Sani (SUARGA: Studi Keberagamaan dan Keberagaman, 2026)
This study examines the Wedang ublek tradition practiced during the Haul (annual commemoration) of Mbah Abdusshomad Jombor in Cipete Village, Cilongok District, Banyumas Regency, Central Java, Indonesia. This research aims to describe the procession of the Wedang ublek tradition and analyze its symbolic meanings using Paul Ricoeur's hermeneutic interpretation theory. This qualitative research employs a cultural studies approach with field research methodology. Data were collected through literature study, in-depth interviews with traditional practitioners, descendants (dzurriyah), and cultural figures, as well as participatory observation and documentation. The findings reveal that the Wedang ublek tradition is an integral part of the Haul Mbah Abdusshomad Jombor commemoration, conducted annually on the 14th of Dzulhijjah in the Islamic calendar. The tradition involves serving a distinctive beverage called "wedang ublek" (a mixture of coffee, coconut milk, palm sugar, and water) accompanied by complementary dishes of "krawu" and "sega aking." The hermeneutic analysis demonstrates that this tradition embodies multiple layers of meaning: (1) as a form of selametan (communal thanksgiving) representing gratitude to Allah SWT; (2) as a medium for almsgiving and sharing blessings with the community; (3) as a means of strengthening social bonds and silaturahmi (kinship ties); and (4) as a symbolic embodiment of the "cagak lek" doctrine, which emphasizes spiritual vigilance and night worship. The tradition reflects the harmonious synthesis of Islamic values and Javanese cultural wisdom, demonstrating how local communities preserve religious heritage while maintaining their cultural identity. Keywords: Wedang ublek Tradition; Haul; Symbolic Meaning; Hermeneutics; Paul Ricoeur; Javanese Islamic Culture